Islamic Business Ethics in the Digital Age: An Analysis of the Principles of Honesty and Transparency in E-Commerce - Umi Iriani; Chelsi Hestivik; Farhan Attoilah; Hartono Hartono (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study aims to analyse the application of Islamic business ethics principles, particularly honesty and transparency, in e-commerce practices in the digital era. The research method employs a Systematic Literature Review (SLR) using the PRISMA 2020 protocol to systematically identify and analyse relevant scholarly literature published between 2018 and 2025. The selection process yielded 28 articles, which were analysed using thematic analysis to identify key patterns and concepts related to digital business ethics. The findings reveal four main themes: digital gharar, information transparency, trustworthiness in digital transactions, and digital manipulation. The results indicate that honesty and transparent product information significantly contribute to building consumer trust and customer loyalty. At the same time, practices such as fake reviews and price manipulation remain ethical challenges in the e-commerce ecosystem. In conclusion, the implementation of Islamic business ethics principles plays a strategic role in strengthening consumer trust and supporting sustainable, fair, and transparent digital business practices